2017
DOI: 10.1149/2.0161704jss
|View full text |Cite
|
Sign up to set email alerts
|

Seebeck Coefficient Measurements of Polycrystalline and Highly Ordered Metal-Organic Framework Thin Films

Abstract: In this work highly oriented Surface Anchored Metal-Organic Framework (SURMOF) films were fabricated quasi-epitaxial and were electrically characterized by Seebeck analysis and benchmarked against random polycrystalline MOF films loaded with tetracyano-quinodimethane (TCNQ) infiltration. The horizontal Seebeck coefficient of the oriented SURMOF films and the random polycrystalline MOF films parallel to the sample surface was measured and has been discussed. The isotropic random polycrystalline MOF films exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28] (Table SI1) (Table S2). [34][35][36] These values are comparable to other classes of thermoelectric materials such as nanostructured materials (Bi2S3 nanowires 37 ), metal oxides (Ca0.8Dy0.2MnO3 38 ) and conducting polymers (poly(3,4-ethylenedioxythiophene):polystyrenesulfonate/polypyrrole/paper 39 ).…”
Section: Introductionsupporting
confidence: 59%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28] (Table SI1) (Table S2). [34][35][36] These values are comparable to other classes of thermoelectric materials such as nanostructured materials (Bi2S3 nanowires 37 ), metal oxides (Ca0.8Dy0.2MnO3 38 ) and conducting polymers (poly(3,4-ethylenedioxythiophene):polystyrenesulfonate/polypyrrole/paper 39 ).…”
Section: Introductionsupporting
confidence: 59%
“…In 2014, some of us applied a radically new approach to impart electrical conductivity to MOFs by incorporating the redox-active molecule TCNQ (7,7,8,8-tetracyanoquinodimethane) in the pores of Cu 3 BTC 2 (also known as HKUST-1; BTC = 1,3,5-benzenetricarboxylate). 8 Since then, this striking observation has been confirmed by other groups; 9 , 10 however, the detailed nature of the host–guest complex and the conductivity mechanism are mainly unsolved. It is proposed that TCNQ bridges two Cu dimer units via two geminal nitrile groups, which is strongly supported by both theory and spectroscopic data.…”
Section: Introductionmentioning
confidence: 53%
“…Higher conductivities in TCNQ@Cu 3 (BTC) 2 compared to the pristine MOF were corroborated by other reports. 245 , 254 , 255 However, Schneider et al 245 and Thürmer et al 256 showed that partial or full conversion of Cu 3 (BTC) 2 into the dense coordination polymer Cu(TCNQ) (σ ∼ 0.1 S/cm 82 , 257 ) upon exposure to TCNQ proceeded under certain conditions. These works highlighted the importance of verifying the phase composition of MOFs after treatment with redox-active species and raise the question of whether the formation of a highly conductive parasitic phase contributes to the improved conductivity.…”
Section: Guest-promoted Transportmentioning
confidence: 99%